Principles of Capital Financing and Capital Charging in Health Care Systems - Sussex, Jon (World Bank, Washington, DC, 2013)
Most health care systems could improve their efficiency in using physical capital - buildings and equipment. Health care systems in which assets are provided by governments or donated by aid organizations generally have only weak incentives for those assets to be used efficiently. Wrongly located or inappropriate facilities, poorly utilized and maintained, are a result. This Discussion Paper summarizes the principles of effective, efficient, and equitable capital financing and capital charging in health care systems. It reviews the options for putting these principles into practice and refers to the limited literature on the impacts of those options. The objectives, principles, and practicalities of implementing capital charging arrangements are set out. The relative benefits and costs of points along the following dimensions are described and summarized: applying capital charges just to newly acquired assets or also to those already in existence; using notional or real capital charges; the time profile of charges; and the asset valuation basis adopted.